THE INFLUENCE OF USER ACTIVITY AND ENVIRONMENTAL CHARACTERISTICS DIMENSIONS ON SENSE OF PLACE IN CITY PARKS - Ivan Danny Dwiputra; Angela Christysonia Tampubolon; Hanson E. Kusuma (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
City parks have certain environmental characteristics and accommodate various types of activities that affect the sense of place of the user. This study was conducted with the aim of identifying the dimensions of user activities and environmental characteristics, and sense of place levels related to city parks, as well as the causal relationships between them. Qualitative research was done using an online survey with open-ended questions. The collected text data were analyzed using content analysis. Quantitative research was done using an online survey with closed-ended questions that were compiled based on the results of the qualitative research analysis. The collected numerical data were analyzed by factor analysis and multivariate regression analysis. The analysis revealed four user activity dimensions (recreation, social interaction, work, and sports and hobby), seven environmental characteristics dimensions (natural environment, design, facilities, comfort, location, proximity, and entertainment), and two sense of place dimensions (compatibility with a place and dedication to a place). The dimension compatibility with a place tended to be influenced by the accessibility and visual quality of a park (location, natural environment, and park design), while the dimension dedication to a place tended to be influenced by user engagement (sport and hobby, and facilities).